Reproducibility of cerebral blood flow, oxygen metabolism, and lactate and N-acetyl-aspartate concentrations measured using magnetic resonance imaging and spectroscopy - Madsen, Signe Sloth; Lindberg, Ulrich; Asghar, Sohail; Olsen, Karsten Skovgaard; Møller, Kirsten; Larsson, Henrik Bo Wiberg; Vestergaard, Mark Bitsch (Frontiers in Physiology, 2023)
In humans, resting cerebral perfusion, oxygen consumption and energy metabolism demonstrate large intersubject variation regardless of methodology. Whether a similar large variation is also present longitudinally in individual subjects is much less studied, but knowing the time variance in reproducibility is important when designing and interpreting longitudinal follow-up studies examining brain physiology. Therefore, we examined the reproducibility of cerebral blood flow (CBF), global cerebral metabolic rate of oxygen (CMRO2), global arteriovenous oxygen saturation difference (A-V.O2), and cerebral lactate and N-acetyl-aspartate (NAA) concentrations measured using magnetic resonance imaging (MRI) and spectroscopy (MRS) techniques through repeated measurements at 6 hours, 24 hours, 7 days and several weeks after initial baseline measurements in young healthy adults (N=26, 13 females, age range 18-35 years). Using this setup, we calculated the correlation, limit of agreement (LoA) and within-subject coefficient of variation (CoVWS) between baseline values and the subsequent repeated measurements to examine the longitudinal variation in individual cerebral physiology.CBF and CMRO2 correlated significantly between baseline and all subsequent measurements. The strength of the correlations (R 2 ) and reproducibility metrics (LoA and CoVWS) demonstrated the best reproducibility for the within-day measurements and generally declined with longer time between measurements. Cerebral lactate and NAA concentrations also correlated significantly for all measurements, except between baseline and the 7-day measurement for lactate. Similar to CBF and CMRO2, lactate and NAA demonstrated the best reproducibility for within-day repeated measurements.The gradual decline in reproducibility over time should be considered when designing and interpreting studies on brain physiology, for example, in the evaluation of treatment efficacy.